Influence of Rainfall and Rainy day On Oil Palm Production 8, 16, and 19 years Old in Sei Dadap PT. Perkebunan Nusantara III Persero - Abdurrahman Zailani; Irsal Irsal; Mariati Mariati (Universitas Sumatera Utara, 2018)
The Influence of rainfall and rainy day on oil palm production 8, 16, and 19 Years Old in Sei Dadap PTPN III Persero supervised byIrsaland Mariati.The climate like rainfall and rainy day is very influential to the growth and productivity of oil palm. The oil palm is a plant that requires large amounts of water than other crops. This research was to determine the effect of rainfall and rainy day as well as the correlation of both on oil palm production in plants aged 8, 16 and 19 years old. The research was conducted at PTPN III Sei Dadap Sub-district Sei Dadap District Asahan Province of North Sumatera from April up to June 2016. This research used primary data available in company administration. Primary data for the purposes of data analysis includes the production of fresh fruit bunches (FFB); component production data as total bunches, average bunches weight, and total of productive trees; rainfall data and rainy day monthly in 2011, 2012, and 2013. The analysis method used are double linier regression and correlation analysis. Model tested by classic asumption consists of normality test, heteroskedasticity test, multicollinearity, and autocorelations test by using statistic software SPSS.v.22 for windows. The regression analysis shows that rain fall and rainy day variables significant with alpha 5% (Sig < α 0.05) to increase the production of FFB at the age of 16 and 19 years and unsignificanted to increase the production of FFB at the age 8 years. This is because the rainfall is not evenly distributed throughout the year and less than optimal for the growth and production of FFB. From the results of the classical assumption test conducted to determine whether the multiple regression equation feasible or not to use the regression equation to conclude that the oil palms aged 8, 16, and 19 years are qualified. Correlation results in plants was 8, 16, and 19 years with two-way analysis test at 1% level showed variable rainfall and rainy days have a strong relation, and the real (positive) direction. The correlation values of rainfall and rainy days are 0.838 with significant level < α 0,01